The Moderating Role of Financial Literacy in Improving Performance Through Digital Economy Impact - Dewi, Resty Yusnirmala; Herawati Khotmi (Lembaga Penelitian Universitas YARSI, 2025)
The objective of this study is to examine how social media, e-commerce, digital payments, and financial literacy influence the performance of micro, small, and medium enterprises (MSMEs). It also aims to analyze the moderating role of financial literacy in the relationships between social media, e-commerce, digital payments, and MSME performance. The study addresses the issue of limited understanding and adoption of digital economy practices among MSMEs. Using a quantitative approach, data from 109 MSMEs, sampled through probability sampling from a population of 33,964, were analyzed via Structural Equation Modeling (SEM) using SmartPLS4. The findings reveal that while digital payments positively influence MSME performance, e-commerce, social media, and financial literacy do not directly affect it. However, financial literacy moderates the relationship between social media and MSME performance but does not influence the relationships involving e-commerce and digital payments. This underscores the need for MSMEs to enhance their financial literacy and e-commerce knowledge to thrive in the digital economy. The study's novelty lies in highlighting financial literacy as a moderating factor between social media and MSME performance, offering new insights into its critical role in fostering MSME growth in the digital age.